To the freeholders and freemen of the city and county of New-York : [Six lines from Luke] : from the above texts, it manifestly appears, that the lawyers were the oppressors of the people . - Philanthropos, active 1768 ([Printed by John Holt], 1768)
Opposing the election of lawyers to the New York Assembly. Signed on page 2: Philanthropos.